Evaluasi Kebijakan Pendelegasian Wewenang dalam Mengelola Pendidikan Menengah - Steiven Orland Ngongira; Ade Iriani (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2020)
Abstract The purpose of this research is evaluating for delegation of implementation policy from Education Office of North Molucas Province to the Educational Institutional branch in managing secondary education in Morotai Island District. The delegation policy based on the governor of North Maluku Regulation number 45 in 2018,  about the duties, function, task description of the department branch office of the Provincial Education, and culture Office of North Maluku. This research using a goal free evaluation model, which measures the implementation, influence of implementation and factors that affect the implementation and Factors that affect the implementation tasks and functions of the office in managing secondary education in Morotai Island District. Data to collected through observations, interviews and document studies. Data analysis are done with a quality data analysis. The results of the research areas follows: (1) Implementation of tasks and functions of the branch of Education office does not carried out effectively that cause problems with the administration of personneal services; (2) Influence of task implementation and function of Education Office branch raises positive and negative impacts. (3) Factors that affect the implementation tasks and functions of the branch of the office in managing secondary education is communication and facilities as well as infrastructure. Abstrak: Tujuan penelitian ini adalah untuk mengevaluasi implementasi kebijakan pendelegasian wewenang Dinas Pendidikan Provinsi Maluku Utara ke Cabang Dinas Pendidikan dalam mengelola pendidikan menengah di Kabupaten Pulau Morotai. Kebijakan Pendelegasian ini berdasarkan Peraturan Gubernur Maluku Utara nomor 45 Tahun 2018, Tentang Tugas, Fungsi dan Uraian Tugas Jabatan Cabang Dinas pada Dinas Pendidikan dan Kebudayaan Provinsi Maluku Utara. Penelitian ini menggunakan model evaluasi goal free yaitu mengukur implementasi, pengaruh implementasi dan faktor-faktor yang memengaruhi pelaksanaan tugas dan fungsi Cabang Dinas Pendidikan dalam mengelola pendidikan menengah di Kabupaten Pulau Morotai. Data dikumpulkan melalui melalui observasi, wawancara dan studi dokumen. Analisis data dilakukan dengan analisis data kualitatif. Hasil dari penelitian yaitu: (1) implementasi tugas dan fungsi Cabang Dinas Pendidikan, belum terlaksana dengan efektif sehingga menimbulkan permasalahan pada pelayanan administrasi kepegawaian; (2) pengaruh implementasi tugas dan fungsi Cabang Dinas Pendidikan menimbulkan pengaruh positif dan negatif. (3) faktor-faktor yang memengaruhi implementasi tugas dan fungsi Cabang Dinas Pendidikan dalam mengelola pendidikan menengah yaitu komunikasi, sarana dan prasarana.